Mechanisms of extrinsic alkali incorporation in CIGS solar cells on flexible polyimide elucidated by nanoscale and quantitative analyses. (January 2020) - Kim, Kihwan; Jeong, Inyoung; Cho, Yunae; Shin, Donghyeop; Song, Soomin; Ahn, Seung Kyu; Eo, Young-Joo; Cho, Ara; Jung, Chanwon; Jo, William; Kim, Jin Hyeok; Choi, Pyuck-Pa; et al.
Abstract: In this work, Cu(In, Ga)Se2 (CIGS) solar cells on polyimide (PI) substrates were fabricated using a low-temperature three-stage co-evaporation process. To enhance device performance, the CIGS films were extrinsically doped with alkali (Na and K) using an in-situ post deposition treatment (PDT). To account for mechanisms of extrinsic alkali incorporation in CIGS solar cells on flexible polyimide, the alkali dopant concentrations in the film bulk (intragrain and grain boundary) and the surface chemistries/band structures were quantitatively investigated with various advanced characterization methods. In addition, the effects of the PDT sequences on the resulting device performance were studied with a particular emphasis on the characteristics of CIGS surfaces. By controlling the alkali incorporation into the CIGS absorber films, flexible lightweight CIGS thin-film solar cells with an efficiency of approximately 19% were obtained. Graphical abstract: Image 1 Highlights: Mechanisms of alkali incorporation in CIGS film were investigated. Nanoscale and quantitative analyses were used to understand the alkali incorporation. Importance of CIGS surface chemistries/band structures was addressed. Approximately 19%-efficiency CIGS solar cells on flexible PI were demonstrated.